Characterization of orange peel pectin and effect of sugars, L-ascorbic acid, ammonium persulfate, salts on viscosity of orange peel pectin solutions - Kar, F; Arslan, N (Elsevier Sci Ltd, 1999)
Anhydrogalacturonic acid, methoxyl, acetyl, ash contents and optical rotation of pectin obtained by a HCl extraction procedure (90 degrees C, pH = 2.5, 90 min) were found to be 74.30, 12.15, 0.37, 6.07% (DM basis) and +252 degrees respectively. The degree of methylation was found to be over 50%, indicating that the orange peel pectin had a high methoxyl content. The reduced viscosities of orange peel pectin obtained by the HCl extraction procedure were measured in aqueous solutions and in the presence of dextrose, maltose and dextrin. Dextrose and maltose were found to increase the reduced viscosity of pectin solutions whereas dextrin decreased it. The viscosity-enhancing effect of dextrose and maltose can be interpreted in terms of the decrease in dielectric constant of the solvent, dehydration action, and hydrogen bonding formation. The specific fluidity of pectin solutions has been observed to be directly proportional to time through the depolymerization effect of L-ascorbic acid. When the concentrations of the pectin solutions were increased in the presence of ammonium persulfate, the increase in the ratio of reduced viscosity to initial reduced viscosity was higher. In addition, the effect of some salts on the viscosity of the pectin solution was examined. The viscosity of the pectin solutions decreased in the presence of salts. When the salt concentration increased, great decreases were observed in the low salt concentrations. (C) 1999 Elsevier Science Ltd. Ali rights reserved.
Keywords: orange peel pectin; anhydrogalacturonic acid; viscosity